Multiattribute Decision Making Using Multiperiod Probabilistic Weighted Fuzzy Axiomatic Design. Issue 4 (9th August 2017) - Karatas, Mumtaz
ABSTRACT: Axiomatic Design is a methodology that provides a framework to systematically analyze the transformation of customer needs into functional requirements and design parameters. Decision‐makers use Weighted Fuzzy Axiomatic Design ( w FAD) in cases where there is imperfect information, and decision criteria have different priorities. In this paper, the w FAD approach is extended to situations which include uncertainty in future events and decision payoffs. In particular, we consider multiple future scenarios with different probabilities and time‐dependent decision payoffs for each system range (SR). For such decision problems, we propose the Multiperiod Probabilistic Weighted Fuzzy Axiomatic Design (MPP‐ w FAD) methodology. The methodology utilizes probabilistic scenario analysis and SR forecast data to assist decision makers in attaining better decisions with improved expected payoffs. As a case study, we apply MPP‐ w FAD to tackle a multiattribute industry selection problem in Turkey and show the impact and usability of the method.